Auto-grasping algorithm of robot gripper based on pressure sensor measurement - Almassri, Ahmed M. M.; Wada, Chikamune; Wan Hasan, Wan Zuha; Ahmad, Siti Anom (Universiti Putra Malaysia Press, 2017)
This paper presents an auto grasping algorithm of a proposed robotic gripper. The purpose is to enhance the grasping mechanism of the gripper. Earlier studies have introduced various methods to enhance the grasping mechanism, but most of the works have not looked at the weight measurement method. Thus, with this algorithm, the weight of the object is calculated based on modified Wheatstone Bridge Circuit (WBC) which is controlled by programmable interface controller (PIC) method. Having this approach introduces and improves the grasping mechanism through an auto grasping algorithm. Experimental results show that an auto grasping algorithm based on pressure sensor measurements leads to a more precise grasping measurement and consequently enhance the sensitivity measurement as well as accurate movement calibration. Furthermore, several different grasping objects based on the proposed method are examined to demonstrate the performance and robustness of our approach.